Prevalence of cytomegalovirus (CMV) infection among infants and correlation between cmv pcr with clinical outcomes in Hospital Universiti Sains Malaysia (HUSM) - Norjihan, Abdul Hamid (2020)
Introduction: Congenital Cytomegalovirus (CMV) infection is the leading infectious cause of congenital hearing loss and neurodevelopmental disability. The aims of this study were to describe the prevalence and clinical manifestations of infants with CMV infection in Hospital Universiti Sains Malaysia (HUSM) and to determine its correlation between CMV PCR with clinical outcomes. Materials and Methods: A total of 648 blood samples of infants requested for TORCHES screening from January 2018 to December 2018 were sent to Microbiology laboratory in Hospital Universiti Sains Malaysia (HUSM). The samples were tested for anti-CMV IgM and IgG by electrochemiluminiscence immunoassay (ECLIA) method. Infants with first serum sample of IgM and IgG antibody titre suggestive of Cytomegalovirus infection were requested for second serum sample at two to four weeks interval together with plasma samples for Cytomegalovirus DNA viral load and maternal sample for serological analysis. The plasma CMV DNA quantification was performed using real-time PCR assays. Correlation of CMV viral load with clinical outcomes were analysed using the point- biserial correlation Results: The prevalence of symptomatic Cytomegalovirus infection among infant in HUSM was 6.48 % (42/648). Out of 648 cases, 196 cases had paired sera samples and 97 cases were tested for CMV PCR. Only 39 cases were positive for CMV PCR. Based on serological and PCR results, the cases were categorised into three groups: acute CMV infection (n = 42), passive immunity (n = 113) and inconclusive (n =41). Clinical presentations for acute Cytomegalovirus infection were small for gestational age (64%), jaundice (52.3%), presumed sepsis (21.4%), abnormal hearing assessment (9.5%), hepatitis (9.5%), ocular problem (4.7%), prematurity (4.7%), rash (2%), microcephaly (2.3%), cerebral calcification (2.3%) and thrombocytopenia (2.3%). There was positive moderate significant correlation between CMV viral load and abnormal hearing assessment and weak positive significant correlation between CMV viral load and abnormal ocular finding. Conclusion: The prevalence of CMV infection among infants in our center was comparable with previous studies. However, the prevalence of cCMV among infants was lower that might be due underdiagnosed. Abnormal hearing assessment, presumed sepsis, CMV hepatitis and rash were significantly associated with acute symptomatic CMV infection among infants. There were significant correlation between CMV viral load with abnormal hearing assessment and abnormal ocular findings.